Financial Decision Dynamics of Generation Z in Yogyakarta: The Impact of Digital Marketing, Brand Image, and Financial Inclusion on Islamic Bank Products - Mawaddah, Isnaini; Syah, Toufan Aldian (Profit : Jurnal Inovasi Ekonomi dan Bisnis, 2024)
The aim of this study is to determine the extent to which Digital Marketing, Brand Image, and Financial Inclusion influence Generation Z's decisions in the Yogyakarta region regarding the use of Indonesian Sharia Bank products. Bank Syariah Indonesia (BSI) is the largest Islamic bank in Indonesia but has a relatively small number of customers compared to other banks, particularly considering Indonesia's large Muslim population. This research employs a quantitative approach, with data collected from 100 samples using questionnaires as the primary data source. The results show that the Digital Marketing variable (X1) has a significant influence on Generation Z's decisions. The Brand Image variable (X2) has a positive and significant influence, while the Financial Inclusion variable (X3) also has a positive and significant influence. These findings suggest that a better Brand Image of Bank Syariah Indonesia in the eyes of users will impact their choice to use Indonesian Sharia Bank products